Danhong Injection for the Treatment of Hypertensive Nephropathy: A Systematic Review and Meta-Analysis - Li, YiZhuo; Yan, Shihai; Qian, Lichao; Wu, Lihua; Zheng, Yawei; Fang, Zhuyuan (Frontiers in Pharmacology, 2020)
Objective: Danhong Injection (DHI) has been widely used in the treatment of various diseases in China for a long time. The objective of this systematic review was to evaluate the efficacy of DHI combined with antihypertensive drugs for hypertensive nephropathy. Methods: Seven databases were searched from inception to September 21st, 2019. Randomized controlled trials comparing DHI combined with antihypertensive drugs versus antihypertensive drugs alone were extracted. The primary outcome was microalbuminuria (mALB). The second outcomes included systolic blood pressure (SBP), diastolic blood pressure (DBP), and serum creatinine (SCr). Result: Fifteen studies were included in this study. Meta-analysis indicated DHI combined with antihypertensive drugs exhibited advantages over antihypertensive drugs alone in reducing mALB [WMD = -12.86, 95% CI (-14.72, -11.0), P < 0.01], lowering SBP [WMD = -2.84, 95% CI (-4.56, -1.12), P = 0.001] and DBP [WMD = -2.38, 95% CI (-4.34, -0.43), P = 0.017], and decreasing SCr [WMD = - 40.45, 95% CI (-55.69, -25.21), P < 0.01]. Conclusion: The combination of DHI with antihypertensive drugs appears to be more effective than antihypertensive drugs alone for the treatment of hypertensive nephropathy. A moderate duration (less than or equal to 4 weeks) of DHI is reasonable, and an overlong term of DHI should be avoided, according to the results of subgroup analysis.